An Audit on the Role of Sentinel Lymph Node Biopsy (SLNB) in High Risk of Invasion DCIS and Encysted Papillary Carcinoma (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: ductal carcinoma in situ; sentinel lymph node biopsy; encysted papillary carcinoma